Penerapan Paket Teknologi LEISA (Low External Input and Sustainable Agriculture) pada Lahan Pasca Penambangan Timah di Kecamatan Mendo Barat, Bangka - Mustikarini, Eries Dyah; Lestari, Tri; Santi, Ratna (Universitas Bangka Belitung, 2010)
Bangka Belitung Island has alot of degraded lands due to tin mining activities. Because the people do not use those for farming, the lands will be the places for unconventional mining continuously. Based on this situation, the researcher did some extension activities and tarinings which aimed to introduce LEISA technology to the farmers in the period of June-Desember 2009 in Kace Village, Mendo Barat Subdistrict, Bangka Regency. The results indicated that 73.81% of the participants strongly agreed and nobody disagreed to the implementation of LEISA in post-tin mining land. the percentage of public confidence to the success of LEISA program in increasing the farmersâ income was about 24.39% for the confidence level >81% and 36.59% for 61-80% of the confidence level. SWOT analysis showedÂ that government and security officials needed to guarantee the safety and the legal certainlyof agricultural development in post-tin mining land, and also needed to be a partnership among the farmers,Â institutions, relevant organizations and government to help the fulfillment of the material and means of agricultural production that can not be supplied by the people independently.Â